Awareness and Compliance of Site Engineers with Road Safety and Traffic Management: The Case of 2nd District, Negros Oriental - Macayan, Ryan; Saguban, Lucelle; Macayan, Wilma (Journal of Interdisciplinary Perspectives, 2025)
This descriptive-correlational study assessed the awareness of and compliance with the Department of Public Works and Highways (DPWH) road safety and traffic management protocols among field engineers on civil works projects in Negros Oriental’s 2nd District. Using a validated questionnaire, data were gathered from 100 engineers (60 from private contractors and 40 from the DPWH). Engineers reported very high awareness of road safety (mean = 4.50) and traffic management standards (mean = 4.41); however, their self-rated compliance, although still high, was lower (mean = 4.13). Spearman’s correlation confirmed that greater awareness predicted stronger compliance (ρ = .52, p < .001). Field implementation, however, was hindered by four key challenges: motorist non-compliance (89%), vandalism of signage (73%), constrained traffic flow management (62%), and insufficient hands-on training (60%). By quantifying the awareness–compliance gap and pinpointing context-specific barriers in a developing-country setting, the study deepens understanding of why high protocol knowledge does not always translate into safe on-site practices. The findings urge the DPWH and contractors to (1) intensify on-site monitoring and enforcement partnerships, (2) allocate budgets for rapid signage replacement, (3) deliver scenario-based training to site personnel, and (4) launch community road safety campaigns. Implementing these measures can convert engineers’ strong knowledge base into consistently safe work zones, reducing accidents and project delays across Philippine infrastructure projects.